‘UNIVERSITY IN A GARDEN’ AN ATTRACTION FOR FOREIGN STUDENTS ENROLLING IN USM - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 16 March 2016 – ‘University in a Garden’ sums up the impression of USM in being the first choice for international students, such as Ph.D candidate, Muhammad Imran Sarwar, 32, from Lahore, Pakistan, who is currently pursuing his studies at the National Advanced IPv6 Centre (NAv6), USM after completing his Master’s degree at USM.